Influência de manobras de válvulas na identificação de vazamentos em redes de distribuição de água utilizando dados transientes e algoritmo genético - Souza, Antônio Carlos de (2016)
In the process of water supply through water distribution networks can happen losses of water resources associated with various causes, such as leaks, metering errors and unauthorized consumption. With the advancement of computer mathematical models increasingly complex have allowed the emergence of advanced techniques in matters relating to the design and optimal design of water distribution networks, including, for example, leak identification technique. The method used to solve the inverse problem is the use of transient data for calibration leak through genetic algorithm (MTI-AG) and for solution of partial differential equations of motion for the flow of the transient is used the method of characteristics (MOC) . In the three networks in study analyzes the transient severity of the effect caused by changes in the type of valve maneuver where several simulations were performed and compared the results with the initial permanent conditions, showing the method employed efficiency.